Leakage Characteristics and Experimental Research of Staggered Labyrinth Sealing - Na Wang; Yongbing Cao; Zhencong Sun; Shixin Tang; Seung-Bok Choi (Lubricants)
The staggered labyrinth seal is widely used in aerospace, transportation, mining, and other fields due to its advantages of adapting to high speed, reliable sealing performance, and low or even frictionless friction between dynamic and static rotors. The traditional calculation method of labyrinth seal leakage mostly focuses on the fact that the internal medium is an ideal gas and only considers a single effect, which cannot accurately describe the leakage of liquid medium lubricating oil in the labyrinth seal. Therefore, this study focuses on the leakage characteristics of labyrinth seals, and it proposes a leakage calculation method based on liquid medium in view of the shortcomings of existing calculation methods under liquid medium conditions. By considering the thermodynamic and frictional effects of the staggered labyrinth sealing, the resistance loss and thermodynamic effect of the lubricating oil in the sealing cavity were analyzed. The flow field analysis was used to reveal the leakage law of lubricating oil under different conditions, and the factors such as total inlet pressure, spindle speed, and sealing clearance were considered. Finally, the leakage characteristics of the staggered labyrinth seal and the accuracy of the calculation method of the leakage of the staggered labyrinth seal under multiple effects were revealed through experimental verification. This study provides useful guidance for the performance optimization of labyrinth seals in practical applications.